Investigating Use of Crushed Glass as Partial Replacement of Sand to Improve Finish Mortar Strength. - Ashaba, Dennis (Kabale University, 2025)
The need to value wastes and the opening towards the use of sand replacement materials, both in mortars and concretes, with the purpose of promoting increased sustainability of building materials, were the grounds for this work that aims at the formulation of mortars with crushed glass aggregate. In this experimental study, the production of finish mortar using finely crushed glass and surface finish blocks using crushed coarse glass are investigated. The mechanical properties of the mortar composite of crushed glass at different percentage compositions are investigated. The test results show that the partial replacement of sand by finely crushed glass at a level of 20% by weight has a significant effect on the compressive strength of mortar as compared with the control sample because of the pozzolanic nature of the fine glass. Results indicate the pozzolanic reactivity of this waste and open possibilities for the use of this material in mortars. Mortar is a mixture of cement, sand, and water made into a thick paste that is used to bind two surfaces with each other and is used as a binding material between stones, concrete, and bricks. Mortar is typically a matrix that contains cement, lime, alkali-activated binders, fine aggregates (sand/rock powder), adequate water, and possibly superplasticizers or viscosity modifying agents added. The chemical composition of mortars indicates that they are most commonly composed of Calcium oxide and silicon dioxide. The high calcium oxide content and low magnesium oxide content probably mean that lime was provided from calcareous stones rather than dolomitic.